2021
DOI: 10.1177/0272989x20987221
|View full text |Cite
|
Sign up to set email alerts
|

When Is a Harm a Harm? Discordance between Patient and Medical Experts’ Evaluation of Lung Cancer Screening Attributes

Abstract: Background A shared decision-making (SDM) process for lung cancer screening (LCS) includes a discussion between clinicians and patients about benefits and potential harms. Expert-driven taxonomies consider mortality reduction a benefit and consider false-positives, incidental findings, overdiagnosis, overtreatment, radiation exposure, and direct and indirect costs of LCS as potential harms. Objective To explore whether patients conceptualize the attributes of LCS differently from expert-driven taxonomies. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Our qualitative data provide additional insights on participant perceptions of the tool regarding usability and usefulness. The design of our value assessment measures was based on qualitative studies conducted with veterans regarding how they perceived and valued the potential benefits and harms of LCS [ 30 ]. In usability testing, the value assessments were completed without difficulty, with some participants commenting that they enjoyed responding to these scales and found them helpful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our qualitative data provide additional insights on participant perceptions of the tool regarding usability and usefulness. The design of our value assessment measures was based on qualitative studies conducted with veterans regarding how they perceived and valued the potential benefits and harms of LCS [ 30 ]. In usability testing, the value assessments were completed without difficulty, with some participants commenting that they enjoyed responding to these scales and found them helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Stakeholder focus groups (clinicians) and structured interviews (veterans) further informed the content and features of the prototype LCSDecTool [ 30 ]. The LCSDecTool was designed to (1) use in advance of or during a primary care clinical visit where LCS may be initiated, (2) ensure that veterans understand the key benefits and potential harms of LCS, (3) help veterans weigh the benefits and potential harms of LCS, (4) provide resources for smoking cessation and mental health treatment, (5) support communication with their provider regarding this decision, and (6) include a clinician portal to streamline the use of the tool with a clinician in the clinical setting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…89,90 Overdiagnosis and subsequent treatment of indolent cancers do cause harm, and those risks should be factored into screening decisions, 91 yet the appetite for screening has been strong for decades, thanks to public health campaigns promoting screening programs and emphasizing the benefits of early detection. 92,93 More recent studies continue to show a strong preference for screening, often with little recognition of the downsides 94,95 but also when participants do understand the limitations. 24 A widely recommended remedy for this overscreening is informed decision making, where patients are offered information about the risks and benefits of screening as well as not screening.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with research that indicates patients may conceptualize cancer screening, including associated harms and benefits, differently than experts or providers with whom they are engaged in SDM processes. 20 Likewise, there is potential for tension between stakeholder groups in the purpose of using DAs to achieve shared decisions that warrants further exploration. For example, in our study, PCPs preferred sharing information on multiple screening modalities, while some experts suggested that evidence-based modalities unavailable in patients’ health care contexts could be omitted from DAs.…”
Section: Discussionmentioning
confidence: 99%